2021
DOI: 10.2174/1573403x15666190603111056
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Renal Outcomes of Incretin-based Therapies: A Review of Recent Clinical Trials

Abstract: Background: To report the cardiovascular and renal effects of incretin-based therapies. Method: The studies of clinical trials on incretin-based therapy published in medical journals from years 2010 to 2017 were comprehensively searched using MEDLINE and EMBASE with no language restriction. The studies were reviewed and the cardiovascular and renal risks reported were recorded. Results: Incretin-based therapeutics represent novel and promising anti-diabetes drugs, the direct cardiovascular actions of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“… 49 Incretin-based therapies have also been developed and are reported to be effective and well tolerated, leading to lowering the risk of cardiovascular events. 50 …”
Section: Discussionmentioning
confidence: 99%
“… 49 Incretin-based therapies have also been developed and are reported to be effective and well tolerated, leading to lowering the risk of cardiovascular events. 50 …”
Section: Discussionmentioning
confidence: 99%
“…Kyriakos et al . reviewed clinical trials and concluded that this medication is showed to be effective in lowering the risk of cardiovascular disease without burden the renal function [ 4 ]. In addition, a new group of hypoglycemic drugs has been used to treat diabetes type 2.; the active sodium glucose co-transporter (SGLT2) or SGLT2 inhibitors.…”
mentioning
confidence: 99%